A Cosmopolitan Ideal: Paul's Declaration 'Neither Jew Nor Greek, Neither Slave Nor Free, Nor Male and Female' in the Context of First-Century Thought - Neutel, Karin B. (The Library of New Testament Studies, 2015)
What did Paul mean when he declared that there is 'neither Jew nor Greek, neither slave nor free, nor male and female' (Galatians 3:28)? While many modern readers understand these words as a statement about human equality, this study shows that it in fact reflects ancient ideas about an ideal or utopian community. With this declaration, Paul contributed to the cultural conversation of his time about such a community. The three pairs that Paul brings together in this formula all played a role in first-century conceptions of what an ideal world would look like. Such conceptions were influenced